Nursing care for people living with HIV: a narrative review - Moura, Taysa Juliana Santos de; Luna, Izabel Cristina de Oliveira; Nascimento, Carlos Queiroz do (JRG Journal of Academic Studies, 2024)
This study aims to describe the role of nursing in the care of patients living with HIV/AIDS. This is a narrative of the literature that used scientific articles indexed in the LILACS, MEDLINE, and BDENF databases in English, Portuguese, and Spanish, published between 2019 and 2024. The presence of nurses is essential, but their role is often limited to diagnosis, while monitoring and follow-up are the responsibility of physicians. It is necessary to expand the role of nurses in the comprehensive care of patients with HIV, recognizing their vital contribution to advances in responses to the HIV/AIDS pandemic. In conclusion, the role of nursing in the comprehensive care of patients with HIV/AIDS plays a crucial role in both therapeutic strategies and psychological support for HIV-positive individuals.